Role of Operon aaoSo-mutT in Antioxidant Defense in Streptococcus oligofermentans - Zhou, Peng; Liu, Lei; Tong, Huichun; Dong, Xiuzhu (PLOS ONE, 2012)
Previously, we have found that an insertional inactivation of aaoSo, a gene encoding L-amino acid oxidase (LAAO), causes marked repression of the growth of Streptococcus oligofermentans. Here, we found that aaoSo and mutT, a homolog of pyrophosphohydrolase gene of Escherichia coli, constituted an operon. Deletion of either gene did not impair the growth of S. oligofermentans, but double deletion of both aaoSo and mutT was lethal. Quantitative PCR showed that the transcript abundance of mutT was reduced for 13-fold in the aaoSo insertional mutant, indicating that gene polarity derived from the inactivation of aaoSo attenuated the expression of mutT. Enzymatic assays were conducted to determine the biochemical functions of LAAO and MutT of S. oligofermentans. The results indicated that LAAO functioned as an aminoacetone oxidase [47.75 nmol H2O2 (min·mg protein)–1]; and MutT showed the pyrophosphohydrolase activity, which removed mutagens such as 8-oxo-dGTP. Like paraquat, aaoSo mutations increased the expression of SOD, and addition of aminoacetone (final concentration, 5 mM) decreased the mutant’s growth by 11%, indicating that the aaoSo mutants are under ROS stress. HPLC did reveal elevated levels of cytoplasmic aminoacetone in both the deletion and insertional gene mutants of aaoSo. Electron spin resonance spectroscopy showed increased hydroxyl radicals in both types of aaoSo mutant. This demonstrated that inactivation of aaoSo caused the elevation of the prooxidant aminoacetone, resulting the cellular ROS stress. Our study indicates that the presence of both LAAO and MutT can prevent endogenous metabolites-generated ROS and mutagens. In this way, we were able to determine the role of the aaoSo-mutT operon in antioxidant defense in S. oligofermentans.